2010
DOI: 10.1016/j.fcr.2009.10.013
|View full text |Cite
|
Sign up to set email alerts
|

A staggered maize–legume intercrop arrangement robustly increases crop yields and economic returns in the highlands of Central Kenya

Abstract: Smallholder farmers in East-Africa commonly intercrop maize (Zea mays L.) with grain legumes to maximize utilisation of land and labour, and attain larger crop yields. Conventionally, one legume line is intercropped between each pair of maize lines. This study evaluated the potential of a modified two-bytwo staggered arrangement (MBILI) to increase crop yields and economic benefits in two sites in Central Kenya with contrasting soil fertility levels during 7 consecutive seasons. Common beans (Phaseolus vulgari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
109
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 181 publications
(125 citation statements)
references
References 19 publications
13
109
0
3
Order By: Relevance
“…Further to that, a delay in sowing of four weeks was long enough to avoid interspecific competition for light and nutrients and allow a good establishment of both maize and roselle (Flores-sanchez et al, 2013). Despite the beneficial effects of the intercropping to the cereal crops, it may also quicken soil nutrient depletion, particularly for phosphorous, due to added efficient use of soil nutrients and higher exclusion through the harvested crops (Mucheru-Muna et al, 2010). However, Chalka and Nepalia (2006) found that maize intercropped with soybean produced significantly lower NPK depletion and higher N uptake.…”
Section: Resource Usementioning
confidence: 99%
“…Further to that, a delay in sowing of four weeks was long enough to avoid interspecific competition for light and nutrients and allow a good establishment of both maize and roselle (Flores-sanchez et al, 2013). Despite the beneficial effects of the intercropping to the cereal crops, it may also quicken soil nutrient depletion, particularly for phosphorous, due to added efficient use of soil nutrients and higher exclusion through the harvested crops (Mucheru-Muna et al, 2010). However, Chalka and Nepalia (2006) found that maize intercropped with soybean produced significantly lower NPK depletion and higher N uptake.…”
Section: Resource Usementioning
confidence: 99%
“…The value of K SS was higher than K CP and K CT in mixed cropping (Table 3), indicating an advantage of S. splendida over the other legume in the mixed cropping system. The presence of legume improved the growth of S. splendida (Mucheru-Muna et al, 2010). Legume root systems did not give tough competition to the grass (Refliaty et al, 2009), as the grass acquire N from legumes through the decomposition and mineralization of N-rich legume plant litter and N transfer from the legume to grass (Pirhofer-Walzl et al, 2012).…”
Section: Competition Indicesmentioning
confidence: 99%
“…Others investigators have shown that intercropping of cereals and legumes produce higher grain yields than either sole crop (Mpairwe et al, 2002;Mucheru-Muna et al, 2010). In such intercropping, the yield development of the cereal component (Dahmardeh et al, 2010).…”
Section: Introductionmentioning
confidence: 99%